Interdisciplinary Integration of the Mother Tongue in the Primary Education System and its Importance - N. B. Adizova; S. U. Olimova (International Journal on Integrated Education, 2023)
In this article, the science of the mother tongue is related to which subjects in primary education, and views on its importance are stated.